2012
DOI: 10.1063/1.3684557
|View full text |Cite
|
Sign up to set email alerts
|

InGaN/GaN multiple-quantum-well light-emitting diodes grown on Si(111) substrates with ZrB2(0001) buffer layers

Abstract: Multiple-quantum-well light-emitting diode (LED) structures of InGaN/GaN were grown by metalorganic chemical vapor deposition on Si(111) substrates via ZrB2(0001) buffer layers and a GaN template comprising composite AlxGa1-xN (where x lies in the range from 0 to 1) transition layers to minimize cracking due to thermal expansion mismatch between Si and GaN. Photoluminescence and electroluminescence results from the LED structures compared favorably with similar measurements obtained on identical LED structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…[12][13][14] Furthermore, ZrB 2 is reflective and metallic, and its use as a substrate in LEDs minimizes loss of light and simplifies the device geometry as ZrB 2 can be used as one of the ohmic contacts. 15 The crystal structure of bulk ZrB 2 is simple hexagonal with alternating layers of boron and zirconium as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Furthermore, ZrB 2 is reflective and metallic, and its use as a substrate in LEDs minimizes loss of light and simplifies the device geometry as ZrB 2 can be used as one of the ohmic contacts. 15 The crystal structure of bulk ZrB 2 is simple hexagonal with alternating layers of boron and zirconium as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, the epitaxial growth of GaN films on Si substrates still has at least three challenges by now. It is reported that the chemical reactions between Ga and Si can be solved by the insertion of AlN ,9-11 Al 2 O 3 , 12 or ZrB 2 13 buffer layer, to isolate Ga from Si. Second, the large thermal coefficient mismatch (54%) between GaN and Si will induce massive tensile stresses.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to grow thick crack‐free GaN on Si substrates due to the large differences in the lattice constant and the thermal expansion coefficient between GaN and Si. In order to obtain high‐quality GaN on Si substrates with a crack‐free surface, it is necessary to design a relaxation layer before the main GaN growth .…”
Section: Introductionmentioning
confidence: 99%